Pengaruh Pembelajaran Seni Gerak dan Musik Terhadap Perkembangan Motorik Kasar Anak Usia Dini di TK An-Nida - Dinda Salsabila; Faisa Rahma Safira Siregar; Najwa Dwi Aprillia; Hilda Zahra Lubis (An Nafi': Multidisciplinary Science, 2025)
This study aims to determine the effect of learning movement arts and music on the development of gross motor skills of early childhood in Kindergarten. This study uses a qualitative approach with a case study method at An-Nida Kindergarten, Jalan Mister No. 21, Sei Putih, Medan Petisah District, Medan City. Data were collected through observation, interviews, and documentation of teachers and children. The results of the study indicate that learning movement arts and music that is carried out in a structured, fun way, and involves active body movements can improve children's coordination, flexibility, and large muscle strength. Learning movement arts and music also has a positive impact on children's emotional expression and social interaction. These findings indicate that movement arts and music have an important contribution in stimulating the gross motor aspects of early childhood effectively.